Elucidation of morphological behavior on the samarium strontium cobaltite carbonate composite cathode for LTSOFC - Mohammad, Siti Fairus; Ahmad, Sufizar; Abdul rahman, Hamimah; Muchtar, Andanastuti (UR Publishers, 2018)
Samarium strontium cobaltite, Sm0.5Sr0.5CoO3−δ (SSC) and samarium doped ceria, Sm0.2 Ce0.8O1.9 (SDC) carbonate or (SDCC) was used as the new composite cathode powder materials. Composites cathode powder samples with different on weight percentages, 50:50 wt.% of SSC:SDCC, 60:40 wt.% of SSC:SDCC and 70:30 wt.% of SSC:SDCC were chosen to be use in this research work. The prepared samples of composite cathode powders were characterized by using high energy ball milling (HEBM) techniques for LTSOFC application. Characterizations of the composite cathode were performed through energy dispersion spectroscopy (EDS) and field emission scanning electron microscopy (FESEM) analysis. From EDS analysis shows SSC-SDCC composite cathode powders produced via high energy ball milling techniques (HEBM) or mechanochemical activation indicated that all major elements such as sodium, cobalt, samarium, cerium and strontium were well distributed among the composite cathode powders. Nonetheless, the FESEM images revealed HEBM technique can be used to prepare composite cathode powders with high homogeneity. These results showed that SSC-SDCC composite cathode powders, content with 50 wt.% of SDCC revealed a smallest of particle size with good homogeneity of particle to be us as cathode materials for LTSOFC applications.